The Chinese Room Argument in the Context of the Rational Action Theory - MONIN, Maxim Aleksandrovich; TEREKHOVA, Vera Albertovna; LEDENEVA, Elena Vladimirovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article describes a well-known thought experiment of J. Searle called the Chinese Room directed against theories of strong artificial intelligence in the context of longstanding polemic following the publication of Searle's paper as well as his later book "Rationality in Action" (2001). Their radical separation in the framework of his suggested thought experiment was criticized the most as there was seen simplification which did not comply with real theories of artificial intelligence. Searle’s book published in 2001 makes it clear that the philosopher means first of all the difference within the semantics itself: connected mainly with action and syntax.RESUMEN El artículo describe un conocido experimento mental de J. Searle llamado la Sala China dirigida contra las teorías de la inteligencia artificial fuerte en el contexto de una larga polémica tras la publicación del artículo de Searle, así como su libro posterior "Racionalidad en acción" (2001). Su separación radical en el marco de su experimento mental sugerido fue la más criticada ya que se observó una simplificación que no cumplía con las teorías reales de la inteligencia artificial. El libro de Searle publicado en 2001 deja en claro que el filósofo significa ante todo la diferencia dentro de la semántica misma: conectada principalmente con la acción y la sintaxis.